The Use of Social Media in Public Relations Practice: A Study of the Ghana Armed Forces - Yeboah, Veronica Asantewaa (UniMAC - GIJ, 2021)
Social Media has brought significant changes to communication in Public Relations and the security agencies, especially the Ghana Armed Forces (GAF) is not exception. Social media was not used in the practice of Public Relations in the Armed Forces in the past. However, in modern times, the Armed Forces have embraced social media more than ever which is serving them a good purpose when it comes to information sharing. One thing that is the most likely reason for this development is through the Public Relations function of the Armed Forces. As part of doing this, the Armed Forces is establishing social media handles that will keep its relations with internal and external stakeholders and informed them about what they do. The Ghana Armed forces has a Department for Public Relations, and social media has made issues of openness and practicing public relations in the core tenets of the Institute of Public Relations paramount. The study seeks to assess the use of social media in Public Relations practice in the Ghana Armed Forces. A sample of 237 Personnel at the GAF were asked to fill questionnaires whilst six Officers, three of heads different sections of the GAF PR and the other three heads different units of GAF were interviewed. The study revealed that GAF uses social media in its internal and external communications, but only engages in external communications as and when it is needed; GAF often employ open ways of practicing Public Relations with the use of social media and information has to go through a process of approval. It was recommended that, The Ghana Armed Forces should use social media platforms to develop and enhance the performance of the organization by creating new ways of innovation which lead will to more effectiveness and efficiency within the Armed Forces.
THESIS